Biochar Amendment Stimulates Utilization of Plant-Derived Carbon by Soil Bacteria in an Intercropping System - Liao, Hongkai; Li, Yaying; Yao, Huaiying (Frontiers in Microbiology, 2019)
Plant-derived carbon (C) is considered fundamental to understand the interaction between rhizosphere microbes and plants in terrestrial ecosystems. Biochar soil amendment may enhance plant performance via changing soil properties or microbial diversity in the rhizosphere. However, our knowledge of how plant-microbiome associations respond to biochar amendment remains rather limited. Herein, 13CO2 steady-state labeling combined with DNA-SIP (stable isotope probing) was used to characterize the microbial communities contributing to the metabolization of plant-derived C. The diversity of soil microbes active in the utilization of root exudates was determined during biochar amendment in a legume-based intercropping system (Vicia faba L., with Zea mays L.). The results show the biochar application not only changed the soil microbial community structure and diversity in the rhizosphere, but also altered soil microbiome members actively assimilating plant-derived C. There were more labeled microbial species in the biochar-amended soils compared with control soils. In the rhizosphere, relative to the controls the biochar amendment increased the relative abundances of Firmicutes and Bacteroidetes members (i.e., Bacillus, Clostridium, Sporomusa, Desulfosporosinus, and Alicyclobacillus) while decreasing the relative abundance of Proteobacteria members (e.g., Methylobacterium and Sphingomonas) utilizing plant-derived C. In contrast, slow-growing bacterial species of the phylum Acidobacteria, Planctomycetes, and Gemmatimonadetes were barely labeled. The microbes found stimulated by the biochar amendment are known for their ability to fix nitrogen, solubilize phosphorus, or reduce iron and sulfur, which may potentially contribute to the ‘biochar effect’ in the rhizosphere. This study is the first to provide empirical evidence that biochar amendment can alter soil microbiome assimilating plant-derived C; this may have consequences for nutrient cycling and improving plant performance in intercropping systems.